2017
DOI: 10.18203/2320-1770.ijrcog20175020
|View full text |Cite
|
Sign up to set email alerts
|

An audit of extra-uterine pregnancy in a tertiary care facility in Northern India

Abstract: Background: Ectopic pregnancy is the most frequent lethal gynaecological predicament, befalling worldwide in all strata of reproductive women. It remains the leading cause of pregnancy-related first trimester deaths. Though prompt diagnosis has furthered a decline in associated morbidity, an upsurge has been seen in its prevalence owing to a rise in predisposing risk factors. The objectives of this study were to identify incidence, risk factors, and outcome in patients presenting with ectopic pregnancy in a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…The present study determined the prevalence, key management outcomes, and factors associated with the management outcomes of EPs treated in Central Tigray region of Ethiopia. We found that the prevalence of EP was recorded in 5 : 1000 deliveries (0.5%), a finding consistent with studies in Guinea (0.41%) [9], and Papua New Guinea (0.6%) [16]; although different globally, EP accounts for almost 2% [8,9], South Africa (2.2%) [12], and Nigeria (1.1%) [13]. These variations could be linked to differences in environmental conditions (e.g., exposure to toxic materials), the prevalence of related infections (e.g., sexually transmitted infections), and social lifestyle (e.g., smoking).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The present study determined the prevalence, key management outcomes, and factors associated with the management outcomes of EPs treated in Central Tigray region of Ethiopia. We found that the prevalence of EP was recorded in 5 : 1000 deliveries (0.5%), a finding consistent with studies in Guinea (0.41%) [9], and Papua New Guinea (0.6%) [16]; although different globally, EP accounts for almost 2% [8,9], South Africa (2.2%) [12], and Nigeria (1.1%) [13]. These variations could be linked to differences in environmental conditions (e.g., exposure to toxic materials), the prevalence of related infections (e.g., sexually transmitted infections), and social lifestyle (e.g., smoking).…”
Section: Discussionsupporting
confidence: 89%
“…Journal of Pregnancy areas is far better than their rural counterparts, and this may influence the early presentation to EP care and treatment, which is supported by research in Ethiopia and India [8,18]. Consistent with other findings [1,22], women diagnosed with EP and anemia were also at higher risk of unfavorable EP outcome management.…”
supporting
confidence: 70%
See 3 more Smart Citations